Multigenomics Reveals the Causal Effect of Herpes Simplex Virus in Alzheimer’s Disease: A Two-Sample Mendelian Randomization Study - Zhang, Yuwei; Qu, Jiaojiao; Luo, Li; Xu, Zhongshun; Zou, Xiao (Frontiers in Genetics, 2022)
In recent years, the herpes virus infectious hypothesis for Alzheimer's disease (AD) has gained support from an increasing number of researchers. Herpes simplex virus (HSV) is a potential risk factor associated with AD. This study assessed whether HSV has a causal relationship with AD using a two sample Mendelian randomization analysis model. Six single nucleotide polymorphisms (SNPs) associated with HSV-1 and thirteen SNPs associated with HSV-2 were used as instrumental variables in the MR analysis. We estimated MR values of relevance between exposure and the risk of AD using inverse-variance weighted (IVW) method, MR-Egger regression (Egger), weighted median estimator (WME). To make the conclusions more robust and reliable, sensitivity analyses and RadialMR were performed to evaluate the pleiotropy and heterogeneities. We found that anti-HSV-1 IgG measurements were not associated with risk of AD (OR, 0.96; 95% CI, 0.79–1.18; P=0.736), and the same was true for HSV-2 (OR, 1.03; 95% CI, 0.94-1.12; P=0.533). The findings indicated that any HSV infection does not appear to be a genetically valid target of intervention in AD.